A Novel High Speed FPGA Architecture for FIR Filter Design - Sachin B. Jadhav; Nikhil Niwas Mane (Institute of Advanced Engineering and Science, 2012)
This paper presents the details of hardware implementation of linear phase FIR filter using merged MAC architecture. Speed of convolution operation of FIR filter is improved using merged MAC architecture. By exploiting the reduced complexity made possible by the use of sparse powers of two partial products terms coefficients, an FIR filter tap can be implemented with 2B full adders, and 2B latches, where B is intermediate wordlegnth. Word and bit level parallelism allows high sampling rates, limited only by the full adder delay. The proposed architecture is based on binary tree constructed using modified 4:2 and 5:2 compressor circuits. Increasing the speed of operation is achieved by using higher modified compressors in critical path. Our objective of work is, to increase the speed of multiplication and accumulation operation by minimizing the number of combinational gates using higher n: 2 compressors, which is required more for Array multiplier at the time of implementation of array architecture. This novel architecture allows the implementation of high sampling rate filters of significant length on FPGA Spartan-3 device (XC3S400 PQ-208). The simulation result shows convolution output of digital FIR filter which is done using Questa Sim 6.4c Mentor Graphics tool. The experimental test of the proposed digital FIR filter is done using Spartan-3 device (XC3S400 PQ-208)